Changes in Elbow Stress and Ball Velocity During Reduced Effort Pitching: A Marker-Based Motion Capture Analysis. Issue 3 (March 2023) - Fiegen, Anthony P.; Nezlek, Stuart P.; Loushin, Stacy R.; Christoffer, Dan; Verhoeven, Martijn; Kaufman, Kenton R.; Camp, Christopher L.
Background: Baseball pitchers often participate in throwing programs that involve throwing at reduced effort levels to gradually increase the amount of stress experienced across the elbow. It is currently unknown how reduced effort pitching compares with maximum effort with respect to elbow stress and ball velocity. Purpose/Hypothesis: The purpose was to determine the correlation between elbow stress and ball velocity with reduced effort pitching. We hypothesized that decreased perceived effort would disproportionately correlate with elbow stress and ball velocity. Study Design: Descriptive laboratory study. Methods: Ten healthy male high school baseball pitchers threw 5 pitches from a regulation pitching mound at 3 effort levels: maximum effort, 75% effort, and 50% effort. Elbow stress, specifically elbow varus torque, was calculated for all pitches using a validated marker-based 3-dimensional motion capture system. Ball velocity was measured using a Doppler radar gun. Intrathrower variability was calculated for each effort level. Results: Elbow stress and ball velocity decreased with reduced effort throws ( P < .001 and P = .003, respectively). However, the reductions in elbow stress and ball velocity were not proportional. At 75% effort throws, elbow stress measured 81% (intraclass correlation coefficient [ICC], 0.95), and ball velocity measured 90% (ICC, 0.80) of maximum, respectively. At 50% effort throws, elbow stress measured 75% (ICC, 0.93), and ball velocity measured 85% (ICC, 0.87) of maximum. Intrathrower reliability was excellent for elbow stress and ball velocity, with all ICCs ≥0.80. Conclusion: Pitching at a reduced effort level resulted in decreased elbow stress and ball velocity. However, for every 25% reduction in perceived effort, elbow stress decreased by a mean 13%, and ball velocity decreased 7.5%. When baseball pitchers attempt to throw at a reduced effort of maximum, throwing metrics do not decrease proportionately. Clinical Relevance: While pitching at a reduced effort of maximum decreases elbow stress and ball velocity, the decrease is not proportional, subjecting the elbow to more stress than intended. This has significant clinical importance to pitchers, coaches, and medical professionals in the setting of injury prevention and return to sports.